A taxonomic review of the genera Boonea, Chrysallida, Parthenina, Ivara, Fargoa, Mumiola, Odostomella and Trabecula (Gastropoda, Pyramidellidae, Odostomiinae) from Brazil - Pimenta, Alexandre Dias; Absalão, Ricardo Silva; Miyaji, Cintia (Zootaxa, 2009)
The genera Boonea Robertson, 1978, Chrysallida Carpenter, 1856, Fargoa Bartsch, 1909, Ivara Dall & Bartsch, 1903, Mumiola A. Adams, 1863, Odostomella Bucquoy, Dautzenberg & Dollfus, 1883, Parthenina Bucquoy, Dautzenberg & Dollfus, 1883 and Trabecula Dall & Bartsch, 1909 from Brazil are reviewed. Boonea jadisi (Olsson & McGinty, 1958), Boonea seminuda (C. B. Adams, 1839), Chrysallida gemmulosa C. B. Adams, 1850, Ivara terryi (Olsson & McGinty, 1958), Fargoa bushiana Bartsch, 1909, Mumiola gradatula (Mörch, 1876) and Odostomella carceralis Pimenta, Absalão & Alencar, 2000 are confirmed to occur in Brazil. We also present the first records of Parthenina varia (Odé, 1993), Odostomella fonteini (Jong & Coomans, 1988) and Trabecula krumpermanni (Jong & Coomans, 1988) from the region, all, new combinations. Two species, previously reported from the Brazilian coast, could not be confirmed: Boonea bisuturalis (Say, 1822) and Boonea impressa (Say, 1822). Odostomella cf. doliolum (Philippi, 1844) and Parthenina cf. interspatiosa (Linden & Eikenboom, 1992), originally described from the eastern Atlantic, are here recorded from Brazil, although their status remains dubious because of lack of information on their biology and due to lack of morphological and molecular data. One new species is described: Boonea scymnocelata, which can be distinguished from the similar species B. seminuda by its smaller size and immersed protoconch, with no visible nucleus.